Three-Dimensional Sonographic Assessment of Placental Volume and Vascularization in Pregnancies Complicated by Hypertensive Disorders - Almeida Pimenta, Eduardo Jorge de; Silva de Paula, Carla Fagundes; Duarte Bonini Campos, Juliana Alvares [UNESP]; Fox, Karin Anneliese; Francisco, Rossana; Ruano, Rodrigo; Zugaib, Marcelo (Amer Inst Ultrasound Medicine, 2014)
Objectives-The purpose of this study was to evaluate the association between placental volumes, placental vascularity, and hypertensive disorders in pregnancy.Methods A prospective case-control study was conducted between April 2011 and July 2012. Placental volumes and vascularity were evaluated by 3-dimensional sonographic, 3-dimensional power Doppler histographic, and 2-dimensional color Doppler studies. Pregnant women were classified as normotensive or hypertensive and stratified by the nature of their hypertensive disorders. The following variables were evaluated: observed-to-expected placental volume ratio, placental volume-to-estimated fetal weight ratio, placental vascular indices, and pulsatility indices of the right and left uterine and umbilical arteries.Results Sixty-six healthy pregnant women and 62 pregnant women with hypertensive disorders were evaluated (matched by maternal age, gestational age at sonography, and parity). Placental volumes were not reduced in pregnancy in women with hypertensive disorders (P > .05). Conversely, reduced placental vascularization indices (vascularization index and vascularization-flow index) were observed in pregnancies complicated by hypertensive disorders (P < .01; P < .01), especially in patients with superimposed preeclampsia (P = .04; P = .02). A weak correlation was observed between placental volumes, placental vascular indices, and Doppler studies of the uterine and umbilical arteries.Conclusions Pregnancies complicated by hypertensive disorders are associated with reduced placental vascularity but not with reduced placental volumes. These findings are independent of changes in uterine artery Doppler studies. Future studies of the prediction of preeclampsia may focus on placental vascularity in combination with results of Doppler studies of the uterine arteries.
Keywords: arterial hypertension; Doppler study; obstetric ultrasound; placental volume; placental size; placental vascularity; preeclampsia; pregnancy; 3-dimensional power Doppler sonography; 3-dimensional sonography; umbilical arteries; uterine arteries